Sistem Informasi Pengelolahan Arus Kas Pada GKT Antiokhia Malang Berbasis Web Untuk Mempermudah Pelaporan - Diaz, Callista Ivena Anggreani; Sakaria, Setiabudi (J-INTECH (Journal of Information and Technology), 2022)
The Gereja Kristus Tuhan (GKT) Antiokhia is one of the churches in Malang that has an uncomputerized data processing system, especially in the financial section which is still written on the financial cash book. This does not close the possibility of errors either in writing or misacalculations. Therefore, a web based cash flow management system is proposed for churches to process financial data and make financial reports more effective and efficient. This study used observation and interview methods for data collection and systems designed using the PHP programming language with the CodeIgniter 3.0 Framework, and Android Studio with Mysql as the database. At the implementation stage, application testing will be carried out using the black box method, and the results of this financial information system produce a financial dashboard for processing financial cash data consisting of income and expenses as well as financial statements of monthly income and expenses. This application is accessed online through the Website and is equipped with an android application to display financial dashboards and financial reports.